Freud e as expressões do real - Valiati, Lucas (Universidade Federal de São Carlos, 2026)
This dissertation aims to examine the notion of reality in Freud’s thought, starting from the observation that, although ubiquitous, it is mostly mobilized in a functional manner, without a systematic conceptualization. The problem consists in determining how the real manifests itself when it does not lend itself to explicit thematization, remaining as a presupposition that operates between the lines of the texts, in clinical technique, and at the point of contact between distinct epistemological planes. Our temporal delimitation follows the itinerary extending from Freud’s Parisian stay under Charcot (1885-1886) to the psychopathological writings and the supposed abandonment of the seduction theory, around 1897. From a methodological standpoint, we adopt a historical-conceptual investigation that integrates internal analyses of Freudian production with external reconstructions of the scientific context. On this basis, we select as the main axes of analysis: hysteria and neurosis in the fin-de-siècle; the controversies between the schools of hypnotism (Salpêtrière–Nancy); Freud’s experiences and productions with respect to hypnosis; his conceptions as developed from the monograph on aphasias and other contemporary works related to the clinic and to hysteria; the relation of supplementarity between Studies on Hysteria (1895) and the Project for a Psychology (1895); and, finally, the psychopathology of the neuropsychoses of defence and the seduction theory. The results indicate a bivalence between Realität and Wirklichkeit: on the one hand, reality as factuality and given content; on the other, effectiveness as that which acts and produces effects. On the basis of this distinction, we circumscribe differentiated domains of reality — psychic, external, and clinical — and propose the notion of psychic effectiveness, discernible in symptom formation and in dream-work. Moreover, we recognize other genres of expression of the real, such as the effet de réel produced by Freudian clinical writing and the “temporalities of the real” inferred from the ontogenetic series deduced in the Project, within which reality is progressively constituted in the organism through conflict between the internal and the external. We conclude that it is possible to delimit expressions of the real in the Freudian oeuvre, whether in the encounter between epistemological planes (reality thought from the Project and from Aphasias), or in specific works or periods, such as the problem of reality in the first psychopathological conceptions or in the seduction theory.
Freud and the expressions of the real
Keywords: Freud; Psicanálise; Realidade; Epistemologia; Filosofia; Freud; Psychoanalysis; Reality; Epistemology; Philosophy; CIENCIAS HUMANAS::FILOSOFIA::EPISTEMOLOGIA; CIENCIAS HUMANAS::PSICOLOGIA; CIENCIAS HUMANAS::FILOSOFIA; 3. Saúde e Bem-Estar